(untitled) (Journal of Comparative & International Higher Education, 2021)
As collaborative transnational education models are increasing in number globally, this study provides a snapshot of motivations for newly enrolled students at microcampuses in China, Cambodia, Jordan, and Indonesia. This research centers on the influence of country choice for students. We apply Nye’s (1990, 2004) concept of soft power on student motivations and conduct quantitative analysis to trace enrollment influences. Mainly, in this case we find that U.S. soft power potentially influences students abroad to enroll in dual-degree programs. Other motivations related to cost and U.S. culture are apparent influences. Furthermore, findings provide greater insights into emerging trends in international student mobility. Our study also identifies strategies to sustain transnational education ventures in the face of challenges. Implications of this research are especially of use to university stakeholders, faculty leaders and policymakers who are working to advance U.S education on an international platform.